The Philosophy and Psychology of Commitment - Michael, John (Routledge Focus on Philosophy, 2022)
The phenomenon of commitment is a cornerstone of human social life. Commitments make individuals' behavior predictable, thereby facilitating the planning and coordination of joint actions involving multiple agents. Moreover, commitments make people willing to rely upon each other, and thereby contribute to sustaining characteristically human social institutions such as jobs, money, government and marriage. However, it is not well understood how people identify and assess the level of their own and others' commitments. The Philosophy and Psychology of Commitment explores and explains the philosophical and cognitive intricacies of commitment. John Michael considers how commitments motivate us and their often implicit and tacit nature. To flesh out the philosophical framework of his argument he draws on experimental work with young children, adults and human-robot interaction within the context of joint action, considering the role of the emotions and whether very young children are sensitive to commitment. Providing an important account of the nature and operation of commitment, this book is essential reading for those working in philosophy of psychology, cognitive science, experimental philosophy, and social and developmental psychology. It will also be of interest to those working in emerging fields such as human-robot interaction and behavioural economics.